2013
DOI: 10.2217/fon.13.9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Networks in Melanoma Invasion and Metastasis

Abstract: Metastatic melanoma accounts for approximately 80% of skin cancer-related deaths. Up to now there has been no effective treatment for stage IV melanoma patients due to the complexity and dissemination potential of this disease. Melanomas are heterogeneous tumors in which conventional therapies fail to improve overall survival. Targeted therapies are being developed, but the final outcome can be hampered by the incomplete knowledge of the process of melanoma progression. Even if the intracellular pathways are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 121 publications
0
32
0
Order By: Relevance
“…These results suggested that melanocyte migration in the BF might affect B-cell development. Malignant neoplasms of human skin (melanomas) exhibit atypical migration of melanocytes in the lymph nodes1920; therefore, the BF acts as an immune organ that provides the material needed to investigate the effects of melanocytes on the development of B-cells in an ideal environment.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that melanocyte migration in the BF might affect B-cell development. Malignant neoplasms of human skin (melanomas) exhibit atypical migration of melanocytes in the lymph nodes1920; therefore, the BF acts as an immune organ that provides the material needed to investigate the effects of melanocytes on the development of B-cells in an ideal environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a bad prognosis for aggressive invasion and high drug resistance [1]. Invasion gives melanoma cells the ability to break out of tissue compartments and spread locally.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma invasion and metastasis are accompanied by changes in cell morphology and the activation of mechanisms that confer the capability of cell movement (Aladowicz et al, 2013). The networks constructed for target genes of continuously up-regulated or downregulated miRNAs were associated with cell morphology, cell development, DNA replication, and system development.…”
Section: Network Related To Cell Morphology Cell Development and Cementioning
confidence: 99%